Local distribution of orientation relationship and microstructure evolution of lath martensite in an ultra-low-carbon steel. (15th April 2020) - Hayashi, T.; Morito, S.; Ohba, T.
Abstract: Local distribution of orientation relationship between austenite and martensite is quantitatively examined using lath martensite in an ultra-low-carbon steel. Orientation relationship is systematically deviated between near Greninger–Troiano and Nishiyama–Wasserman orientation relationships around variant boundaries of the smallest misorientation pair, which is observed as the most frequent variant pair in the steel. Misorientation between this variant pair is decreased at some boundaries of the pair. Formation mechanism of the pair is discussed using the observed boundary characters. Graphical abstract: Image, graphical abstract